A 3D vascularized bone remodeling model combining osteoblasts and osteoclasts in a CaP nanoparticle-enriched matrix. (May 2016) - Bongio, Matilde; Lopa, Silvia; Gilardi, Mara; Bersini, Simone; Moretti, Matteo
Aim: We aimed to establish a 3D vascularized in vitro bone remodeling model.Materials & methods: Human umbilical endothelial cells (HUVECs), bone marrow mesenchymal stem cells (BMSCs), and osteoblast (OBs) and osteoclast (OCs) precursors were embedded in collagen/fibrin hydrogels enriched with calcium phosphate nanoparticles (CaPn). We assessed vasculogenesis in HUVEC-BMSC coculture, osteogenesis with OBs, osteoclastogenesis with OCs, and, ultimately, cell interplay in tetraculture.Results: HUVECs developed a robust microvascular network and BMSCs differentiated into mural cells. Noteworthy, OB and OC differentiation was increased by their reciprocal coculture and by CaPn, and even more by the combination of the tetraculture and CaPn.Conclusion: We successfully developed a vascularized 3D bone remodeling model, whereby cells interacted and exerted their specific function.